Understanding the characteristics of agricultural land transition in Thiès region, Senegal: an integrated analysis combining remote sensing and survey data - Faye, Bonoua; Du, Guoming; Li, QuangFeng; Sané, Tidiane; Mbaye, Edmée; Zhang, Rui (Frontiers in Environmental Science, 2023)
Adopting an integrated analysis may beis a prominent tool for a coherent understanding of the characteristics of agricultural land transition in developing countries. Hence, using an integrated analysis combining remote sensing and survey data, this investigation aimed to understand the spatial-temporal distribution and intensity of agricultural land transition in Senegal through a case study in the Thiès region. Through ArcGIS and ENVI software, we interpreted the land use types from 2000 to 2020 and the transfer matrix method used to characterize the agricultural land transition. Then, the Pearson correlation coefficient was is used to determine the intercorrelation between natural and socio-economic driving factors of agricultural land use. The main results show that agricultural land transition was about -588.66 km 2 . Grassland was the most crucial land morphology to participate in this transition. Regarding spatial distribution, the highest net transition of agricultural land was recorded in Mont-Rolland (33.22%) and the lowest in Sandiara commune (-41.73%). The temporal distribution is represented in Koul, with -0.35%, and Mont-Rolland commune, with 24.84%. The intensity of agricultural land transition was high in Malicounda commune, at 11.34 %. The social survey also shows a strong relationship between wind erosion and land salinity (0.971) as potential driving factors that may induce agricultural land transition.Based on an integrated method, the contribution of this study enhances the theoretical approach and methodology for assessing the mean potential driving factors in developing countries such as Senegal.Consequently, agricultural land transition in Thiès region was complex and must be implemented with complex and comprehensible policy solutions.